2014
DOI: 10.1161/circulationaha.113.004768
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Risk of Second but Not of First Venous Thrombosis

Abstract: Background-The risk of recurrent venous thrombosis is 2-fold higher in men than in women. In contrast, no such sex difference in the risk of first venous thrombosis has been reported. We hypothesized that, for a first event, a risk difference between the sexes is masked by female exposure to reproductive factors (oral contraception, pregnancy/puerperium, and postmenopausal hormone therapy). Methods and Results-From the Multiple Environmental and Genetic Assessment of Risk Factors for Venous Thrombosis (MEGA) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 30 publications
5
89
1
2
Order By: Relevance
“…23 The higher risk in men than in women of recurrent VTE has been recognized for some time, 24 but only recently has it become clear that this disparity in risk also exists for first events. 25 Although the cause of the risk difference between the genders is not yet known, our results are in line with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…23 The higher risk in men than in women of recurrent VTE has been recognized for some time, 24 but only recently has it become clear that this disparity in risk also exists for first events. 25 Although the cause of the risk difference between the genders is not yet known, our results are in line with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, elevated factor VIII activity has not been previously identified as a risk factor for VTE in glioma patients, although factor VIII activity has been associated with VTE in other patient populations [28, 30]. Likewise, male gender, a VTE risk factor in GBM patients in our study, is a novel finding in glioma patients but has been identified as VTE risk factor in the general population [31, 32]. …”
Section: Discussioncontrasting
confidence: 75%
“…However, limiting our analysis to patients above 45 years of age where hormonally induced VTE in women is unlikely, male sex is still a strong risk factor for a subsequent cancer diagnose. One recent study [18] found an increased risk for first time VTE among men compared to females if female reproductive factors are taken into account. Here they discussed differences in genetic factors as one possible explanation.…”
Section: Discussionmentioning
confidence: 99%